Ethnic Factor in Migration Processes in Turan in the 9TH-12TH Centuries - Khusniddin Mamadaliev (International Journal on Integrated Education, 2021)
The article examines the ethnic factor in the migration processes in Turan in the 9th – 12th centuries. The article briefly discusses the main directions and reasons for the migration of different ethnic groups in the process of migration. The materials of written sources and historical literature used by the author to research historical process of migration. In addition, the process of migration of ethnic groups played an important role in the growth of the number of Turkic peoples in Central Asia, Iran and the Middle East. Also, the article touches upon the topic of free and forced migration, as well as the role of certain rulers in the process of migration.